Educational and Social Trends of Kindergarten Teachers Towards Kinetic Education in Daraa Governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims to study the trends of kindergarten teachers from the educational and social aspects towards kinetic education in order to achieve the objectives of kinetic education, in addition to knowing the differences between the study samples in terms of the variables of "age, experience and social status" in the kindergartens in Daraa Governorate.The sample consisted of (66) teachers distributed over (16) kindergartens in the city of Daraa. Special questionnaires were designed for this purpose, which included (46) items distributed in two directions.After testing the hypotheses, the results showed positive attitudes among kindergarten teachers towards kinetic education from an educational point of view. The results of the research also found that there were statistically significant differences with regard to the trends of the teachers in terms of educational and social terms depending on the variable of age, as for the variables of experience and social status, it was statistically significant in relation to the trends of educational parameters with no significant differences towards social trends for kindergarten teachers, which were very positive Towards movement education.